Quartic Kerr cavity combs: bright and dark solitons - Parra-Rivas, Pedro; Hetzel, Sabrina; Kartashov, Yaroslav V; de Córdoba, Pedro Fernández; Alberto Conejero, J; Aceves, Alejandro; Milián, Carles (Optics letters, 2022)
We theoretically investigate the dynamics, bifurcation structure, and stability of localized states in Kerr cavities driven at the pure fourth-order dispersion point. Both the normal and anomalous group velocity dispersion regimes are analyzed, highlighting the main differences from the standard second-order dispersion case. In the anomalous regime, single and multi-peak localized states exist and are stable over a much wider region of the parameter space. In the normal dispersion regime, stable narrow bright solitons exist. Some of our findings can be understood using a new, to the best of our knowledge, scenario reported here for the spatial eigenvalues, which imposes oscillatory tails to all localized states.